An International Comparison of National Clusters - Alex R. Hoen (European Regional Science Association (ERSA), 2001)
The presence of innovative clusters may positively influence domestic economic growth. If it is possible to identify these clusters, economic growth may be increased even further by developing policy that stimulates innovative clusters. Identifying clusters, however, is not an easy task. Input- output tables provide a possibility to identify clusters of sectors. These so-called meso clusters answer the question as to which sectors firms that work together stem from. Hence, meso-clusters provide a framework which indicates how a cluster may be composed. An earlier analysis identified Dutch meso clusters. This opens the possibility to compare these Dutch clusters with clusters in other countries, which helps to answer two questions. Firstly, it shows which clusters exist in which countries. These clusters highlight difference in the way sectors work together in different countries, which may explain different patterns of specialisation or even different economic growth rates. Secondly, differences between similar clusters in different countries are analysed. These differences may stem from, for example, different sectors in similar clusters or from different levels of innovation, productivity, profitability or different export positions of similar clusters. The present paper uses the cluster identification method to compare national clusters in ten countries: Australia, Canada, Denmark, France, Germany Italy, Japan, The Netherlands, The United Kingdom, and The United States. The most remarkable differences between clusters found in these countries and the most interesting differences between the sectors included in the same cluster in different countries are discussed. This provides insight in the differences of the inter-industry linkages in these countries.
Keywords: 330